2022
DOI: 10.3389/fgene.2022.848926
|View full text |Cite
|
Sign up to set email alerts
|

KIFC3 Promotes Proliferation, Migration, and Invasion in Colorectal Cancer via PI3K/AKT/mTOR Signaling Pathway

Abstract: Background: KIFC3, belongs to kinesin superfamily proteins (KIFs), is well known for its role in intracellular cargo movement. KIFC3 has been identified as a docetaxel resistance gene in breast cancer cells, however, the role of KIFC3 and its potential mechanism in colorectal cancer (CRC) remains elusive.Objectives: We aims to investigate the effects of KIFC3 in proliferation, migration, and invasion in CRC as well as the potential mechanism inside.Methods: We investigated the expression of KIFC3 in the Oncomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…This recombinant oncolytic adenoviruses effectively suppressed cancer cell proliferation, especially when combined with DDP. The findings of the present study suggested that the recombinant oncolytic adenovirus exerts its anti-cancer effect by manipulating the PI3K/Akt signaling pathway, a well-known survival and growth pathway in cancer cells ( 40 , 41 ). However, further investigation is required to confirm these results and to address any potential safety concerns or off-target effects.…”
Section: Discussionmentioning
confidence: 58%
“…This recombinant oncolytic adenoviruses effectively suppressed cancer cell proliferation, especially when combined with DDP. The findings of the present study suggested that the recombinant oncolytic adenovirus exerts its anti-cancer effect by manipulating the PI3K/Akt signaling pathway, a well-known survival and growth pathway in cancer cells ( 40 , 41 ). However, further investigation is required to confirm these results and to address any potential safety concerns or off-target effects.…”
Section: Discussionmentioning
confidence: 58%
“…Regarding p21 regulation, the PI3K/AKT signaling pathway has a vital function, 32 , 33 , 34 and we initially explored whether ZNF687 regulates p21 through the PI3K/AKT signaling mechanism. In our investigation, PI3K/AKT signaling‐related molecules and p21‐related target genes were activated after ZNF687 enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy nding in the study revealed elevated expression of KIFC3 is strongly correlated wiith a poor prognosis in patients suffering from aggressive colorectal cancer (CRC). Inhibition of KIFC3 has shown to impede the proliferation, migration, and invasion of CRC cells, accompanied by a reduction in the number of cells in the S phase 17 . Based on the four KIFs mentioned above (KIF3C, KIF17, KIF24 and KIFC3), we carried out a risk model associated with the characteristics of the four KIFs, and our ndings suggest the risk score function as an independent prognostic predictor for STAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous ndings have revealed that the KIFs are extensively engaged in the development of various tumors, alterations in these genes expression levels are closely correlated with the incidence and progression of various types of cancer 16 . Researchers have reported the role of KIFs in malignancies such as colon cancer 17 , liver cancer 18 , and bladder cancer 19 , making them an indispensable subject of study in gastric cancer research. The majority of KIFs have been recognized as contributors to the development and advancement of gastric cancer, while a few act as tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%